Edukasi Kesehatan Jiwa pada Remaja di SMP Negeri 21 Kabupaten Tanjung Jabung Timur, Jambi - Nasution, Riska Amalya; Meinarisa; Falani, Ilham (Journal of Community Engagement Research for Sustainability, 2023)
Adolescence is a stage of life marked by important developments, namely physical, psychological, emotional, and social aspects. In recent years, adolescent mental health has received increasing attention from experts. This is because the early age of the first episode of mental disorders occurs at the age before 14 years. Adolescents at SMPN 21 Tanjung Jabung Timur do not know about mental health in adolescents. This community service activity aims to help increase the knowledge of young people at SMPN 21 Tanjung Jabung Timur about mental health and how to handle it early if mental health problems occur in friends at school. This community service activity was carried out at SMP Negeri 21 East Tanjung Jabung Regency as a health partner. The methods used are lectures, discussions, pre-test and post-test measurements of mental health conditions in adolescents. The results of the activity showed an increase in adolescent knowledge about mental health after being given mental health education by 74.4%. Mental health education is important to do as an effort to prevent mental health problems in adolescents.